Coordination Problems and Aid-Dependency as Challenges of State-Building in the Fragile States - Utomo, Ario Bimo (Global and Policy Journal of International Relations, 2019)
This article examines the concept of state-building as an imperative need in this globalizing world amidst the existence of fragile states around the world. It begins with a simple question regarding the challenges of state-building in fragile states and what measures can be done to minimalizethe probable negatives. Using secondary source analysis and twocase studiesof state-building in Afghanistan, Somaliland, and Aceh, this research finds that there are exclusively two overarching challenges to state- building. First, there has been a challenge of coordination among different actors, as well as with the respective population in the relevant states; the second is the challenge of creating an effective exit strategy, such as maintaining stability and avoiding aid- dependency after the state-building mission has been finished. Keywords: state-building, fragile states, Afghanistan, Somaliland, Aceh DOI : https://doi.org/10.33005/jgp.v7i01.1813